Antiviral Activity of Shiga Toxin 1: Suppression of Bovine Leukemia Virus-Related Spontaneous Lymphocyte Proliferation - Ferens, Witold A. (American Society for Microbiology, 2000)
Human infections with Shiga toxin (Stx)-producing Escherichia coli (STEC) cause hemorrhagic colitis. The Stxs belong to a large family of ribosome-inactivating proteins (RIPs) that are found in a variety of higher plants and some bacteria. Many RIPs have potent antiviral activity for the plants that synthesize them. STEC strains, both virulent and nonvirulent to humans, are frequently isolated from healthy cattle. Interestingly, despite intensive investigations, it is not known why cattle carry STEC. We tested the hypothesis that Stx has antiviral properties for bovine viruses by assessing the impact of Stx type 1 (Stx1) on bovine peripheral blood mononuclear cells (PBMC) from cows infected with bovine leukemia virus (BLV). PBMC from BLV-positive animals invariably displayed spontaneous lymphocyte proliferation (SLP) in vitro. Stx1 or the toxin A subunit (Stx1A) strongly inhibited SLP. Toxin only weakly reduced the pokeweed mitogen- or interleukin-2-induced proliferation of PBMC from normal (BLV-negative) cows and had no effect on concanavalin A-induced proliferation. The toxin activity in PBMC from BLV-positive cattle was selective for viral SLP and did not abrogate cell response to pokeweed mitogen- or interleukin-2-induced proliferation. Antibody to virus or Stx1A was most effective at inhibiting SLP if administered at the start of cell culture, indicating that both reagents likely interfere with BLV-dependent initiation of SLP. Stx1A inhibited expression of BLV p24 protein by PBMC. A well-defined mutant Stx1A (E167D) that has decreased catalytic activity was not effective at inhibiting SLP, suggesting the inhibition of protein synthesis is likely the mechanism of toxin antiviral activity. Our data suggest that Stx has potent antiviral activity and may serve an important role in BLV-infected cattle by inhibiting BLV replication and thus slowing the progression of infection to its malignant end stage.